Being seen : one deafblind woman's fight to end ableism - Sjunneson, Elsa, 1985- (Tiller Press, an imprint of Simon & Schuster, Inc., 2021)
"A deafblind writer and professor explores how the misrepresentation of disability in books, movies, and TV harms both the disabled community and everyone else"--